PENGARUH GAYA KEPEMIMPINAN DAN PROMOSI JABATAN TERHADAP MOTIVASI KERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA BANDA ACEH - Syarifah Mauli Masyitah; Banta Karollah; Ferdi Nazirun Sijabat; Ayu Fardhilla (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2022)
This study to analyze the effect of leadership style and promotion on work motivation. This research is through a statement/questionnaire. The sample of this study was 33 employees. The results of the research on the partial test of the variable Leadership Style have an effect on Employee Work Motivation at the Banda Aceh Primary Tax. Position Promotion has an effect on Employee Work Motivation at the Banda Aceh Primary Tax Service Office. Then the Simultaneous Test between the variables of Leadership Style and Position Promotion has an effect on Employee Work Motivation at the Banda Aceh Primary Tax Service Office. Partially, leadership style influences employee work motivation at the Banda Aceh Primary Tax with tcount (2.568) > ttable (2.042). Partially, promotion has an effect on employee motivation at the Banda Aceh Pratama Tax Office with a t-value2,932 ) > ttable (2,042). Simultaneously, Leadership Style and Position Promotion affect Employee Work Motivation at the Banda Aceh Primary Tax with Fcount (23,548) > Ftable (3,316).